Aspek Hukum Standarisasi Produk di Indonesia dalam Rangka Masyarakat Ekonomi ASEAN - Deviana Yuanitasari; Helitha Novianty Muchtar (Jurnal Hukum IUS QUIA IUSTUM, 2018)
Standardization is an important aspect for Indonesia in global market competition, especially in the MEA (ASEAN Economic Community). This study raises the issues of, first, the strategy to improve product quality  through  Product  Standardization  in  Indonesia  in  relation  to  MEA  from  the  perspective  of consumer protection law. Second, how ASEAN MRA (Mutual Recognition Arrangement) is adopted by ASEAN  countries  in  the  framework  of  MEA.  The  method  used  in  this  study  is  a  normative  juridical method,  which  includes  research  on  positive  legal  inventory,  research  on  legal  principles,  and  in concreto  legal  research  as  well  as  legal  comparisons.  The  results  indicate  that,  first,  the  strategy  to improve  product  quality  through  national  product  standardization  is  done  by  harmonizing  national regulations to accelerate trade relations and protection of the Southeast Asian market. Second, ASEAN MRA is adopted by ASEAN countries with the use of MRA at the regional level, which can be seen in practice in ASEAN. The MRA concept is used by ASEAN through the ASEAN Framework Agreement on Mutual Recognition Arrangements that is currently contained in the ASEAN MRA used to support the  AFTA  free  trade  regime  that  was  established  to actualize  trade  liberalization  among  ASEAN countries.